Analisis Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja Rumah Sakit (SMK3RS) di Rumah Sakit X - Dewi Merien Sari; Sumihardi, Sumihardi (CV. ALIM'SPUBLISHING, 2026)
Improving public health requires planned efforts through effective health services, in which Occupational Safety and Health (OSH) is crucial for protecting workers from the risk of accidents and work-related illnesses. Hospitals present high occupational risks; however, the implementation of the Hospital Occupational Safety and Health Management System (SMK3RS) at Dr. Achmad Mochtar General Hospital in Bukittinggi is considered suboptimal, particularly due to constraints related to limited human resources and changes in organizational structure. This study aims to analyze the implementation of the Hospital Occupational Safety and Health Management System (SMK3RS) and identify the barriers affecting its effectiveness. The research methods used include qualitative approaches such as in-depth interviews, observations, and document reviews, as well as a quantitative approach through a questionnaire administered to 39 respondents. The research results regarding the input component indicate that written policies have not been updated since 2015, the number of staff is limited to only 2 people, and there is no specific budget allocation for OSH. In the process component, planning has been based on risk management; however, the implementation of disaster and fire drills, as well as periodic health examinations, has not been conducted routinely and comprehensively. Regarding the output component, internal monitoring and evaluation have not been conducted systematically, and incident documentation remains inactive. In conclusion, the implementation of SMK3RS at Dr. Achmad Mochtar General Hospital in Bukittinggi has not been optimal due to challenges related to management commitment, budget, and staff competence.